Investigation on the impact of low carbon packaging design on water resource protection - Yang, Haojie; Hong, Kyungmin; Yu, Runze (Frontiers in Energy Research, 2023)
The protection and effective utilization of water resources is the key to addressing global climate change. The development of low-carbon industries plays an important role in promoting the protection of water resources. Faced with the demand for water resource protection, the article combined measures of green production and consumption, and utilized the concept of low carbon packaging design to study the impact of water resource protection. To analyze the impact of low carbon industries on water resource protection, this article studied the impact of the packaging industry on the ecological environment, including the pollution of traditional packaging materials on water resource environment. Combining the concept of global low carbon development, the low carbon packaging industry structure was implemented and the entire process of packaging production was implemented.From green packaging design to green packaging consumption, the concept of sustainable development was upheld. An empirical analysis was conducted on the impact of low carbon packaging industry on water resource protection using an impact model for analyzing water resource protection. The experimental results showed that after implementing the low carbon packaging industry structure model in Zhejiang Province, China, the efficiency of the region's impact on water resources was as high as 90% or more. After implementing a low carbon industrial structure, the sewage discharge in the region showed a decreasing and stable trend. The sewage discharge in the light industrial zone decreased from 120000 m³ to 80000 m³ . The two water pollutants Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) decreased by 4600 tons and 2200 tons respectively. From this, it could be analyzed that low carbon packaging design could to some extent reduce the carbon emissions caused by packaging production, and reduce pollutants, so as to improve the efficiency of water resource protection and management.